Mammary carcinoma with osteoclast-like giant cells: a case report - Albawardi, Alia Saeed (Int J Clin Exp Pathol, 2014)
Mammary carcinoma with osteoclast-like giant cells is rare, and comprises less that 2% of breast carcinoma cases. Herein, we present a case of a 45-year-old woman who underwent breast lumpectomy and sentinel lymph node biopsy for a solitary well defined breast tumor. Histological examination revealed an invasive tumor composed of ducts, small nests and cribriform formations intermixed with a prominent osteoclast like giant cell component. The background stroma is hemorrhagic with conspicuous hemosiderin deposition. The paper will outline the clinico-pathologic characteristic features of this uncommon subtype as well as the current understanding on the pathogenesis of the osteoclast-like giant cells. The invasive carcinoma and the osteoclast-like giant cells staining patterns using immunohistochemical stains for estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, receptor activator of nuclear-kB, RANK ligand, and matrix metalloproteinase 1 are reported.